-6-9+17q=19q+11

Simple and best practice solution for -6-9+17q=19q+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6-9+17q=19q+11 equation:


Simplifying
-6 + -9 + 17q = 19q + 11

Combine like terms: -6 + -9 = -15
-15 + 17q = 19q + 11

Reorder the terms:
-15 + 17q = 11 + 19q

Solving
-15 + 17q = 11 + 19q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-19q' to each side of the equation.
-15 + 17q + -19q = 11 + 19q + -19q

Combine like terms: 17q + -19q = -2q
-15 + -2q = 11 + 19q + -19q

Combine like terms: 19q + -19q = 0
-15 + -2q = 11 + 0
-15 + -2q = 11

Add '15' to each side of the equation.
-15 + 15 + -2q = 11 + 15

Combine like terms: -15 + 15 = 0
0 + -2q = 11 + 15
-2q = 11 + 15

Combine like terms: 11 + 15 = 26
-2q = 26

Divide each side by '-2'.
q = -13

Simplifying
q = -13

See similar equations:

| 5.77x+1=33.2929+x | | S=54-.08(54) | | F(u)=u^3-10 | | .4x=-.8+2 | | 3-9k-19=-7-10k | | 15+u-22=9(2) | | 6x+35=59 | | -4s--8=142 | | 9x-7-2x=56 | | -4t-15+8t=2t+19 | | 3x+7+2x-1=11 | | 7.8+6=23.16 | | 7.8+6=23.16 | | 126+22+4x=180 | | 6x-15=x+5(3+x) | | (x+3)(x+3)=8x | | 20-16y=-19-19y | | p+4b=120 | | 2x+x+(x+2)=30 | | -208=-21x+212 | | -11-22=33 | | 7(4x-5)-4(6x-5)=-91 | | -2j-20=8j | | 8z=122 | | 65+90+5x=180 | | -3-y-X=0 | | 2x-8=-8x-24 | | 2(4-9w)= | | 57+51+9x=180 | | 6(-2y-16)-2y=-12 | | 6p+b=144 | | -18s+10=-17s |

Equations solver categories